A study on the aerodynamics of a floating wind turbine rotor. (February 2016) - Farrugia, R.; Sant, T.; Micallef, D.
Abstract: Understanding the impact of wave induced effects on the aerodynamic performance of Floating Offshore Wind Turbines (FOWTs) is crucial towards developing floating wind turbines cost-effectively to harness wind energy in deep water sites. The complexity of the wake of an FOWT has not yet been fully understood and both experimental together with numerical techniques are essential in this regard. An open source free-wake vortex code was used to determine whether experimentally-observed effects of the wave motions on floating rotor aerodynamics could be reproduced numerically by the lifting line method. From free-wake simulations on a large scale FOWT, complex wake phenomena were observed under the impact of extreme wave conditions. It was found that the difference between the mean power coefficient under platform surge conditions and the steady power coefficient depends on platform surge frequency, surge amplitude and the rotor operating conditions. Using the results from the free-wake vortex simulations, an analysis of a number of wind turbine wake characteristics under floating conditions was carried out in order to identify possible reasons behind the increase in the aerodynamic torque and thrust variations with tip speed ratio. Highlights: An aerodynamic analysis on a full-scale floating offshore wind turbine (FOWT) rotor is presented using a free-wake code. FOWT operation at high tip speed ratios may result in significant fluctuations in rotor aerodynamic loading. The rotor mean power coefficient highly depends on platform surge frequency and rotor operating conditions. Complex tip vortex interactions are generated at high rotor tip speed ratios, surge frequencies and amplitudes.